ANALISIS KEPUASAN PENGHUNI DAN PERANAN ENVIRONMENTAL INFLUENCES INDIVIDUAL CONSUMERS DAN MARKETER STIMULI PADA KONDOMINIUM MEWAH DI SURABAYA - Timoticin Kwanda; Hasan Oetomo (Civil Engineering Dimension, 2002)
The occupancy rate of luxurious condominiums in Surabaya keep on decreasing. There are many reasons for these problems, among others economic crisis that weakened market-buying capability (external) and decreased preferences to reside (internal). The internal factor comprises of occupant’s satisfaction, environmental influences, individual consumers and marketer stimuli. The purpose of the research is to know according to the assessment of the occupants which of these four factors, is higher and more dominant. The occupants surveyed are the occupants of the luxurious condominiums in Surabaya, such as Paragon, Beverly, Puri Matahari, Regency, Graha Famili, and Puri Darmo. Samples were taken with Purposive Sampling method and collected through questioners. Anova is used to analyse the data with SPS 2000 program. The result showed that there are no significant differences of occupant’s satisfaction, environmental influences, individual consumers and marketer stimuli on the six observed condominiums. Meanwhile according to the mean, occupant’s satisfaction, individual consumers and marketer stimuli are dominant at Puri Matahari, and environmental influences are dominant at Puri Darmo. Abstract in Bahasa Indonesia : Tingkat hunian kondominium mewah di Surabaya terus menurun tajam. Hal yang menjadi penyebabnya antara lain krisis ekonomi yang memperlemah daya beli pasar (eksternal) dan menurunnya minat menempati (internal). Faktor internal adalah kepuasan penghuni, environmental influences, individual consumers dan marketer stimuli. Penelitian ini bertujuan untuk mengetahui penilaian penghuni kondominium mewah di Surabaya, yaitu Paragon, Beverly, Puri Matahari, Regency, Graha Famili, dan Puri Darmo terhadap keempat faktor ini. Ingin diketahui faktor mana yang lebih tinggi dan lebih dominan peranannya. Pengambilan sampel menggunakan metode Purposive Sampling dengan pengumpulan data melalui kuesioner. Analisis data menggunakan Anova dengan program SPS 2000. Hasil analisis menunjukkan bahwa tidak ada perbedaan yang signifikan antara faktor kepuasan penghuni dan peranan environmental influences, individual consumers dan marketer stimuli pada keenam kondominium. Sedangkan berdasarkan rerata diketahui bahwa faktor-faktor kepuasan penghuni, individual consumers, dan marketer stimuli dominan pada Puri Matahari, dan faktor environmental influences dominan pada Puri Darmo.